Reduced Vision with Erythrocyte G6PD Enzyme Status Among the School Children of Dhaka City - Yasmin, Ayesha; Jahan, Nasim; Akter, Rezina (Journal of Bangladesh Society of Physiologist, 2011)
Background: Globally more than 123 million people have impaired visual status due to reduced vision (visual acuity <6/6m) and many of them results into complete or partial blindness. The situation is more crucial in case of children whose reduced vision is usually remain undetected. Apparently healthy children with reduced vision may also found with asymptomatic erythrocyte G6PD enzyme deficiency. Objective: This study has been designed to detect the presence of reduced vision among apparently healthy school children of Dhaka city and also to measure their erythrocyte G6PD enzyme level. Method: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC) during the period of 2007-2008. For this purpose 500 children irrespective of sex and aged 6 to 12 years was selected as study population from different schools of Dhaka city. Children were grouped according to their visual status using Snellen's letter chart (1862). Erythrocyte G6PD enzyme was measured by Spectrophotometric method. Children with normal visual acuity (6/6m) were grouped as group- A (control) and those with reduced visual acuity (<6/6m) were in group B. Erythrocyte G6PD enzyme level was measured and compared between the groups. Results: Statistically significant (p<0.05) number of children (12.8%) were detected to have reduced vision when compared with that of normal vision. Reduced vision was present in most of the male children & it was bilateral type of reduced vision. Mean erythrocyte G6PD enzyme level was almost similar in both groups and no significant (p>0.05) difference was observed when compared between them. Conclusion: This study revealed that reduced vision may present in apparently healthy children. So, earlier detection of reduced vision can help to minimize the visual complications in childhood age. This study also revealed that there is no association between reduced vision and G6PD enzyme deficiency. Key words: Reduced vision; G6PD deficiency; Visual acuity DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8087 J Bangladesh Soc Physiol. 2011 June; 6(1): 64-69